Ultrastable and Responsive Foams Based on 10-Hydroxystearic Acid Soap for Spore Decontamination - Carolina Dari; Fabrice Cousin; Clemence Le Coeur; Thomas Dubois; Thierry Benezech; Arnaud Saint-Jalmes; Anne-Laure Fameau (Molecules, 2023)
Currently, there is renewed interest in using fatty acid soaps as surfactants. Hydroxylated fatty acids are specific fatty acids with a hydroxyl group in the alkyl chain, giving rise to chirality and specific surfactant properties. The most famous hydroxylated fatty acid is 12-hydroxystearic acid (12-HSA), which is widely used in industry and comes from castor oil. A very similar and new hydroxylated fatty acid, 10-hydroxystearic acid (10-HSA), can be easily obtained from oleic acid by using microorganisms. Here, we studied for the first time the self-assembly and foaming properties of R-10-HSA soap in an aqueous solution. A multiscale approach was used by combining microscopy techniques, small-angle neutron scattering, wide-angle X-ray scattering, rheology experiments, and surface tension measurements as a function of temperature. The behavior of R-10-HSA was systematically compared with that of 12-HSA soap. Although multilamellar micron-sized tubes were observed for both R-10-HSA and 12-HSA, the structure of the self-assemblies at the nanoscale was different, which is probably due to the fact that the 12-HSA solutions were racemic mixtures, while the 10-HSA solutions were obtained from a pure R enantiomer. We also demonstrated that stable foams based on R-10-HSA soap can be used for cleaning applications, by studying spore removal on model surfaces in static conditions via foam imbibition.